A trifluoromethyl substituted wide bandgap conjugated polymer for non-fullerene polymer solar cells with 10.4% efficiency. Issue 15 (28th March 2018) - Li, Wanbin; Li, Guangda; Guo, Xia; Wang, Yong; Guo, Huan; Xu, Qingqing; Zhang, Maojie; Li, Yongfang
Abstract : A new wide bandgap copolymer (PBZ-m-CF3 ) based on a trifluoromethyl- p -alkoxyphenyl substituted benzodithiophene unit is designed and synthesized. PSCs based onPBZ-m-CF3 /ITIC with toluene as the solvent show a high PCE of 10.4% with a V oc of 0.94 V, a J sc of 18.4 mA cm −2 and a FF of 60.2%. Abstract : A new wide bandgap copolymer (PBZ-m-CF3 ) based on meta -trifluoromethyl- p -alkoxyphenyl substituted benzodithiophene (BDTP- m -CF3 ) and difluorobenzotriazole (FBTZ) was successfully designed and synthesized for efficient non-fullerene polymer solar cells (PSCs). As a comparative material, a wide bandgap copolymer (PBZ1 ) based on p -alkoxyphenyl substituted benzodithiophene (BDTP) and FBTZ was synthesized by the same method. It was found that introducing trifluoromethyl into the meta -position of the phenyl group led toPBZ-m-CF3 possessing a deeper HOMO energy level of −5.49 eV, a wider optical bandgap ( E optg) of 1.99 eV with a higher extinction coefficient of 6.51 × 10 4 cm −1 at 533 nm and a suitable hole mobility of 7.86 × 10 −4 cm 2 V −1 s −1 in comparison withPBZ1 (a HOMO level of −5.27 eV, an E optg of 1.96 eV with an extinction coefficient of 5.23 × 10 4 cm −1 at 539 nm and a hole mobility of 7.23 × 10 −4 cm 2 V −1 s −1 ). Non-fullerene bulk heterojunction PSCs based onPBZ-m-CF3 as the donor and ITIC as the acceptor were fabricated by using toluene as the solvent and showed a higher PCE of 10.4% with a high V oc of 0.94 V, a J sc of 18.4 mA cm −2, and a FF of 60.2% compared with PSCs based onPBZ1 : ITIC (a PCE of 5.8% with a V oc of 0.74 V, a J sc of 15.7 mA cm −2, and a FF of 49.8%). These results demonstrate that a benzodithiophene unit with meta -trifluoromethyl- p -alkoxyphenyl side chains is a promising candidate as an electron-rich building block for high performance PSCs.